2019
DOI: 10.1002/smi.2914
|View full text |Cite
|
Sign up to set email alerts
|

Stress, savouring, and coping: The role of savouring in psychological adjustment following a stressful life event

Abstract: There is increasing research on the role of savouring positive emotional experience in the context of stress. As such, we need a better understanding of how savouring and coping relate to each other and to psychological adjustment outcomes following a stressful life event. In particular, this study seeks to understand whether savouring is better conceptualized as a coping resource or a coping response. Three hundred people who experienced a highly stressful event in the past year completed measures of impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 58 publications
2
21
0
1
Order By: Relevance
“…Our data showed that the depression and anxiety scores are high in individuals who thought of the pandemic as having a negative impact on their life. Positive coping skills have been reported as a resilient psychological mechanism versus mental disease [ 48 , 49 ]. Research showed positive religious coping is vital in reducing anxiety and depression among HCWs amid the pandemic [ 50 ], implying that negative feelings towards pandemic may form a potential risk on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the depression and anxiety scores are high in individuals who thought of the pandemic as having a negative impact on their life. Positive coping skills have been reported as a resilient psychological mechanism versus mental disease [ 48 , 49 ]. Research showed positive religious coping is vital in reducing anxiety and depression among HCWs amid the pandemic [ 50 ], implying that negative feelings towards pandemic may form a potential risk on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Seeking social support as a means of coping with adversity has been categorized as a problem-focused coping strategy (Samios et al ., 2020) and has been found to effectively reduce stress. Mounting evidence has strongly linked adequate support from managers, co-workers, family, and friends with positive mental health outcomes for both healthcare and non-healthcare professionals during stressful and traumatic events such as calamities, accidents, disasters, and disease outbreaks (Baduge et al ., 2018; Labrague et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, successful mental adjustment to a life-threatening event depends on how an individual with an experience of living with cancer or even terminally ill cancer attempts to retrieve or gain control over the event and over life, and attempts to reestablish self-esteem, along with a positive attitude toward life [ 36 ]. A better mental adjustment indicates less depression, less anxiety, and greater life satisfaction [ 13 ]. It could expand people’s thought–action repertoires and establish resources for coping, which could significantly facilitate good CoQoLO.…”
Section: Discussionmentioning
confidence: 99%
“…Patients’ perceived social support provides a protective factor for mental adjustment [ 8 ]. An earlier study showed that patients with better social support demonstrated better mental adjustment [ 13 ], aided by mental adjustments of close relatives or families in dealing with patients with terminal cancer and the possible death of their loved ones. Some of these concepts include believing death as a distant possibility, trusting that the disease would improve, encouraging people to live in the moment, and making good use of family support and social networks [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation